The handbook of language contact - Hickey, Raymond, 1954- (Blackwell handbooks in linguistics., 2010)
The Handbook of Language Contact offers systematic coverage of the major issues in this field - ranging from the value of contact explanations in linguistics, to the impact of immigration, to dialectology - combining new research from a team of globally renowned scholars, with case studies of numerous languages. An authoritative reference work exploring the major issues in the field of language contact: the study of how language changes when speakers of distinct speech varieties interactBrings together 40 specially-commissioned essays by an international team of scholarsExamines language contac.- Resumé vydavatel